Strategy For The Development of Mrs. Yanti's Coconut Oil Business in Simbang Village, Sub-District Majene Regency - Busman Busman; Syamsul Rahman; Syamsinar Syamsinar; Helda Ibrahim (Jurnal Indonesia Sosial Sains, 2026)
The Mandar coconut oil business is a household industry based on local resources that has economic and cultural value for the people of Majene Regency. However, the sustainability of this business faces various obstacles, especially limited capital, weak marketing management, and high competition with factory oil. This study aims to analyze the development strategy of Mrs. Yanti's Mandar coconut oil business in Simbang Village, Pamboang District, Majene Regency in improving her business performance. The research uses a descriptive qualitative approach with a case study method. Data was collected through observation, in-depth interviews, and documentation, then analyzed using a SWOT analysis approach through the preparation of IFAS, EFAS, and SWOT matrices. The results of the study show that Mandar's coconut oil business has the main strengths in the form of the availability of raw materials, product quality without preservatives, and consumer trust. The biggest opportunity comes from the character of the product as a local food typical of the region and the development of information technology. The results of the SWOT mapping place businesses in the growth quadrant, so the recommended strategy is an aggressive strategy, especially improving product quality, improving packaging, utilizing digital promotional media, and strengthening capital through access to business financing. The implementation of this strategy is expected to improve business performance and the sustainability of the Mandar coconut oil household industry